THE RELEVANCE OF ‘CHARACTER WITNESS’ TESTIMONY IN CRIMINAL CASES IN INDONESIA - Putri, Devita Kartika (Diponegoro Law Review, 2024)
Character witnesses evidentiary relevance remains underexplored in Indonesian academic discourse. This article addresses this gap by examining the circumstances in which character witness testimony holds significance. Using qualitative study referencing eleven court decisions in criminal cases, the research identifies three key contexts where character witness testimony proves relevant. First, it serves to elucidate elements crucial to the assessment of a crime. Second, it aids in determining whether a defendant should be exempted from criminal liability. Third, it may influence sentencing considerations by either mitigating or aggravating the severity of penalties imposed. Moreover, the article examines the limitations inherent in character witness testimony. It highlights that such testimony may lack relevance to provide contextual assistance to the judges Additionally, while character witness testimony can potentially enhance understanding of a defendant's disposition, it cannot serve as sole grounds for conviction. Propensity evidence derived from character witness statements may be considered in sentencing phases to influence severity but cannot independently establish guilt. This article contributes to a nuanced understanding of the role of character witnesses within the Indonesian legal framework, offering insights into their potential impact on judicial decision-making and the boundaries of their evidentiary value in criminal proceedings.